2022
DOI: 10.1111/bph.15776
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal prostaglandin E synthase‐1 is involved in the metabolic and cardiovascular alterations associated with obesity

Abstract: Background and Purpose Microsomal prostaglandin E synthase‐1 (mPGES‐1) is an inducible isomerase responsible for prostaglandin E2 production in inflammatory conditions. We evaluated the role of mPGES‐1 in the development and the metabolic and cardiovascular alterations of obesity. Experimental Approach mPGES‐1+/+ and mPGES‐1−/− mice were fed with normal or high fat diet (HFD, 60% fat). The glycaemic and lipid profile was evaluated by glucose and insulin tolerance tests and colorimetric assays. Vascular functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 63 publications
(85 reference statements)
2
14
0
Order By: Relevance
“…In addition, brachial–ankle PWV values after weight regaining were independent of body weight, high-sensitivity C-reactive protein (hs-CRP), or insulin resistance changes [ 56 ]. However, it is still unknown what impacts a decrease in PWV value after weight reduction the most; whether it depends on changes in adipokines and inflammatory markers or is due to weight reduction per se [ 57 , 58 ].…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%
“…In addition, brachial–ankle PWV values after weight regaining were independent of body weight, high-sensitivity C-reactive protein (hs-CRP), or insulin resistance changes [ 56 ]. However, it is still unknown what impacts a decrease in PWV value after weight reduction the most; whether it depends on changes in adipokines and inflammatory markers or is due to weight reduction per se [ 57 , 58 ].…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%
“…After dissection, vessels were mounted in an isometric myograph (Danish Myo Tech, Aarhus, Denmark). After an equilibration period for 30 min at 37 °C in the organ bath, the arterial diameter for optimal tension development was determined as described [ 34 ]. Segment’s viability was then studied by initial exposure to a high-potasium (K + ) solution (120 mmol/L KCl) in KHS (K + -KHS).…”
Section: Methodsmentioning
confidence: 99%
“…From these images, measurements of internal and external diameters (Di and De) were obtained under passive conditions at each intraluminal pressure using ImageJ software. Structural and mechanical parameters were calculated as described [ 34 ]. Briefly, Cross-sectional area = π/4 × (De 2 − Di 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Human studies have shown a positive correlation between plasma glucose, obesity, and Isg15 mRNA levels in peripheral blood mononuclear cells ( Gonzalez-Amor et al, 2022 ). Moreover, mice fed a high-fat diet (HFD) show increased aortic mRNA expression of Isg15 and other inflammatory genes such as Ccl2 , Il1b , and Tnfa ( Ballesteros-Martinez et al, 2022 ) . Using GEO data base query and related online analytical tools, Sun et al identified ISG15 amongst five genes that were related to both T2M and ovarian cancer, and found that ISG15 expression in ovarian cancer biopsies significantly correlated with patient’s survival time ( Sun et al, 2019 ).…”
Section: Isg15 In Age-related Cardiovascular and Cardiometabolic Dise...mentioning
confidence: 99%
“…A recent study of the ISG15 pathway in vascular pathophysiology found that Isg15 expression is increased in the aortas of hypertensive animals and in angiotensin II-treated vascular cells and macrophages (Gonzalez-Amor et al, 2022). The same study found that ISG15 expression in human peripheral blood mononuclear cells positively correlated with systolic and diastolic blood pressure and with carotid intima-media thickness and also found elevated ISG15 expression in human and mouse abdominal aortic aneurysms (Gonzalez-Amor et al, 2022). Moreover, Isg15-null mice were found to be protected against angiotensin II-induced hypertension, elastin remodeling, vascular stiffness, endothelial dysfunction, and expression of inflammatory and oxidative stress markers (Gonzalez-Amor et al, 2022).…”
Section: Hypertension and Cardiac Hypertrophymentioning
confidence: 99%